Traditional medicine and COVID-19: influence on the recovery and satisfaction of the Tsáchila nationality - Walter Patricio Castelo Rivas; David Isrrael Gallardo Córdova; Allison Juliana Zúñiga García; Jesica Liliana Cueva Toaquiza; Ángel Ramón Sabando García (Revista Información Científica)
Introduction: traditional medicine is a healing alternative used by indigenous nationalities with the aim of promoting recovery from certain diseases, where ancestral processes were an option to mitigate the repercussions of COVID-19.